Effects of pine bark amended with goat manure as tomato (Solanum lycopersicon L) seedlings growing media using the float system - Madziwa, Munyaradzi (Midlands State University, 2017)
Pine bark is locally available in Zimbabwe and is widely in vegetable seedling production. However, it lacks essential nutrients for seedling growth. Goat manure was used to supplement nutrients when pine bark is used as growing media. The main object of the study was to determine the effect of pine bark amended with goat manure on tomato seedling emergence and seedling quality parameter which were stem diameter and stem length. The study was carried out at the Tobacco Research Board which is located 15 kilometers East of Harare at an altitude of latitude 170 55' S and longitude 310 08' E. The experiment was laid out in a 3 X 3 Factorial in a Completely Randomized Design with three replicates. The experiment had nine treatments with three different growing media which were un-amended pine bark, pine bark amended with goat manure and pine bark amended with Calcium carbonate (CaCO3). It also had three fertilizer rates which were 0 ppm, 75 ppm and 150 ppm float fertilizer. Results from this study showed that the different media and fertilizer combinations had a significant effect (P<0.05) on seedling emergence, stem diameter and stem length. From the results pine bark amended with goat manure significantly increase seedling emergence, stem diameter and stem length compared to un-amended pine bark and pine bark amended with CaCO3. A combination of pine bark amended with goat manure and 75 ppm float fertilizer had a significantly high emergence percentage, stem length and stem diameter compared to other media and fertilizer combinations.